Transformasi Tradisi Perang Obor Jepara Dalam Perancangan Coffee Table dengan Metode ATUMICS - Masabdi, Habib Hasan Abdi; Indarto, Indarto; Rosalina, Neni Nurul (Jayapangus Press, 2025)
The Perang Obor tradition in Jepara is one of the local cultural heritages that contains spiritual, symbolic and community identity values. This research aims to explore and transform the visual and philosophical elements of the tradition into contemporary furniture design in the form of a coffee table. The approach used is culture-based design with the application of the ATUMICS (artifact, technique, utility, material, icon, concept, shape) analysis method as a systematic framework in the design process. Data was obtained through visual observation of the implementation of traditions, documentation of cultural elements, and literature studies on symbolic values and product design aspects. The analysis process was conducted to determine the elements of tradition that can be maintained, modified, or eliminated in the realization of modern design. The results show that the main symbol in the form of a torch can be interpreted visually through the shape of table legs, decorative patterns, and a combination of materials such as wood and rattan that represent the flame and simplicity of local values. The final design not only fulfills functional and aesthetic aspects, but also conveys a strong cultural narrative, making the furniture a medium of preservation and expression of Jepara's cultural identity. This innovation proves that the ATUMICS method is effective in integrating traditional heritage into modern, contextually relevant design products. The design results also have the potential to expand the scope of culture-based design in the local creative industry that is oriented towards the preservation of traditional values.